Factors Associated with Patient Delay in Diagnosis of Pulmonary Tuberculosis in a District - Choudhari, M; Jha, N; Yadav, D K; Chaudhary, D (Journal of Nepal Health Research Council, 2013)
Background: Tuberculosis is one of the major public health problems that is affecting large number of people each year including Nepal. Methods: A descriptive cross sectional study was conducted in Sunsari district of Nepal. The patients with pulmonary tuberculosis patients from 14 DOTS centers in the District were interviewed. Face to face interview by using structured questionnaire was used for data collection. Extra pulmonary tuberculosis and patients under Category II were excluded from the study. Data entry and analysis was carried out in SPSS version 16. Pearson Chi square test was used to test the association between outcome variable with different categorical independent variables. Results: Out of the total 215 patients, 91 (65.6%) were male, 109 (50.7%) were from rural residence, 69 (32.1%) were illiterate, 147 (68.4%) were married and 141 (66%) were sputum positive. The overall median patient delay was 42 days. About 145 (67.4%) of the patients had delayed their first consultation for more than 30 days. The patient delays were 56 out of 68 (82.4%) in age above 50 years patients, 121 out of 161 (75.2%) in married patients, 37 out of 45 (82.2%) in Kirats, 55 out of 69 (72.7%) in illiterates and 95 out of 124 (76.6%) in those who travel the distance of 2 or more km from the place of residence to health facility. Conclusions: Since the time duration before the treatment and diagnosis in TB patients is long, this study emphasizes the need of awareness about symptoms of tuberculosis among general population. Keywords: district; factors for delay; patient delay; tuberculosis.